The Effect of Project Based Learning (PBL) in Writing Skill - Indah Rahmalia; Sawitri Utari (EDULIA: English Education, Linguistic and Art Journal, 2021)
This study aimed to determine whether writing using the Project Based Learning (PBL) method is effective for students or not. This research is experimental. The population in this study was 62 first-grade students of SMA N 1 Kec. Lareh Sago Halaban in 2017/2018 Academic year. The sample was selected using the cluster random sampling technique. Class X IPA 2 as an experiment was taught using the Project Based Learning (PBL) method, and class X IPA 4 as a control using ordinary teaching. The research instrument was a written test. Then, this instrument can be trusted because it uses inter-rater reliability. To analyze the students' test scores, the formula was used by Sudijono. To determine whether the Project Based Learning method is effective or not in teaching writing, the test scores were tested using the t-test formula to answer the hypothesis. The results showed that t-count <t-table (-0.93 <2,000). In conclusion, there is no significant effect of teaching writing. It can be concluded that the PBL method is not effective in teaching writing. Keywords: Project Based Learning (PBL) Method, Teaching Writing, Writing